2022
DOI: 10.3390/ijerph19042272
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Physical Burden of Older Persons’ Household Caregivers: The Effect of Household Handrail Provision

Abstract: The household handrail is necessary for dependent older people to perform their daily living activities, improve caregiving competency, and reduce caregiver burden. This study aimed to explore physical burden levels and examine their association with handrail provision among caregivers in older people’s households in Phuttamonthon District, Thailand, in 2017. This study used the physical dimension of the Caregiver Burden Inventory to quantify the levels of physical burden among 254 caregivers in households wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Fifteen articles were retained for analysis (Table 2). [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] Studies reported in the articles were conducted in several countries and employed a variety of quantitative, qualitative, and mixed methodologies. Technologies examined in the articles were of 3 general types: physical or mobility aids, sensor and monitoring systems, and socialization enhancement technologies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen articles were retained for analysis (Table 2). [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] Studies reported in the articles were conducted in several countries and employed a variety of quantitative, qualitative, and mixed methodologies. Technologies examined in the articles were of 3 general types: physical or mobility aids, sensor and monitoring systems, and socialization enhancement technologies.…”
Section: Resultsmentioning
confidence: 99%
“…While the body of literature is not extensive enough to evaluate efficacy, it does provide a starting point for understanding how several types of assistive technology impact paid caregivers working with older adults. Articles consistently reported tangible benefits that physical aids, including grab bars and handrails, 34,36 bidet seats, 35 and transfer devices, 32,33 provided in reducing physical strain associated with caregiving tasks. These devices also helped paid caregivers complete their tasks more efficiently and decreased anxiety about safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be due to many younger generations had migrated to urban areas (Ahmad & Ismail, 2014). The increasing number of older people will have an impact on the burden of aged care services to children or sandwich households (Phetsitong & Vapattanawong, 2022;Knickman & Snell, 2002), and to the government.…”
Section: Literature Review Older Person and Povertymentioning
confidence: 99%
“…Despite the gains of a better life wellbeing, the problem of poverty in old age remains a worrisome issue. This is because poverty and income inequality in old age cause a person to experience failure due to considerations early in life (Phetsitong & Vapattanawong, 2022;Knickman & Snell, 2002). This can result in them being forced to live without adequate basic needs for a long period of time.…”
Section: Introductionmentioning
confidence: 99%